Characterization of the Population of the Sulfur-Oxidizing Symbiont of Codakia orbicularis (Bivalvia, Lucinidae) by Single-Cell Analyses - Caro, Audrey (American Society for Microbiology, 2007)
We investigated the characteristics of the sulfur-oxidizing symbiont hosted in the gills of Codakia orbicularis, a bivalve living in shallow marine tropical environments. Special attention was paid to describing the heterogeneity of the population by using single-cell approaches including flow cytometry (FCM) and different microscopic techniques and by analyzing a cell size fractionation experiment. Up to seven different subpopulations were distinguished by FCM based on nucleic acid content and light side scattering of the cells. The cell size analysis of symbionts showed that the symbiotic population was very heterogeneous in size, i.e., ranging from 0.5 to 5 μm in length, with variable amounts of intracellular sulfur. The side-scatter signal analyzed by FCM, which is often taken as a proxy of cell size, was greatly influenced by the sulfur content of the symbionts. FCM revealed an important heterogeneity in the relative nucleic acid content among the subclasses. The larger cells contained exceptionally high levels of nucleic acids, suggesting that these cells contained multiple copies of their genome, i.e., ranging from one copy for the smaller cells to more than four copies for the larger cells. The proportion of respiring symbionts (5-cyano-2,3-ditolyl-terazolium chloride positive) in the bacteriocytes of Codakia revealed that around 80% of the symbionts hosted by Codakia maintain respiratory activity throughout the year. These data allowed us to gain insight into the functioning of the symbionts within the host and to propose some hypotheses on how the growth of the symbionts is controlled by the host.